Pengaruh Pendidikan Kesehatan Dengan Media Audiovisual Terhadap Sikap Ibu Tentang Inisiasi Menyusu Dini - Fatmah Zakaria (Universitas Aisyiyah Yogyakarta, 2017)
The promotion of exclusive breastfeeding can be policy makers, service providers and the wider community. Know the effect of health education with audiovisual media on mother’s attitude about early breastfeeding initiation (IMD). The research design used is quasi experiment non equivalent. Non sampling sampling technique with consecutive sampling with 30 respondents in each group (control and intervention). Data analysis was done by bivariate analysis using non parametric test because the data were not normally distributed with p value 0,05 and multivariate analysis using linear regression. The results showed that there was an increase of knowledge and attitude after being given health education with audiovisual media seen at mean value of attitude 12,8 ± 0,37 with p value 0,000 α 0,05. Health education with audiovisual media influences the mother’s attitude toward early initiation of breastfeeding.